2013
DOI: 10.5198/jtlu.v6i2.296
|View full text |Cite
|
Sign up to set email alerts
|

Spatial modeling of bicycle activity at signalized intersections

Abstract: This paper presents a methodology to investigate the link between bicycle activity and built environment, road and transit network characteristics, and bicycle facilities while also accounting for spatial autocorrelation between intersections. The methodology includes the normalization of manual cyclist counts to average seasonal daily volumes (ASDV), taking into account temporal variations and using hourly, daily, and monthly expansion factors obtained from automatic bicycle count data. To correct for weather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 22 publications
(23 reference statements)
0
11
1
Order By: Relevance
“…The combined influence may contribute to a higher bicycle volume in locations near beach areas and with better bicycle facilities. Surprisingly, the model revealed a negative association between the presence of a school and bicyclist volume, which contradicts previous studies conducted in Canada [11,84]. However, a study conducted in the United States suggested that the number of students (ages 5 to 18) who walk or bike to school decreased sharply in recent years due to increased traffic collisions, lack of sidewalks, and urban sprawl [85].…”
Section: Exposure Modeling and Risk Quantificationcontrasting
confidence: 68%
“…The combined influence may contribute to a higher bicycle volume in locations near beach areas and with better bicycle facilities. Surprisingly, the model revealed a negative association between the presence of a school and bicyclist volume, which contradicts previous studies conducted in Canada [11,84]. However, a study conducted in the United States suggested that the number of students (ages 5 to 18) who walk or bike to school decreased sharply in recent years due to increased traffic collisions, lack of sidewalks, and urban sprawl [85].…”
Section: Exposure Modeling and Risk Quantificationcontrasting
confidence: 68%
“…A wide range of factors are identified as determinants of bicycle use in the current literature (Strauss & Miranda-Moreno, 2013). This section provides a review by synthesizing the effects of the built environment, transportation policies, socio-demographics, and time-varying factors on bicycle use.…”
Section: 2mentioning
confidence: 99%
“…For example, intersections that punctuate bicycle facilities have shown to be particularly vexing; the body of literature examining intersections along off-street paths is burgeoning (Phillips et al 2011;Schepers et al 2011;Sorton and Walsh 1994;Strauss and Miranda-Moreno 2013). In the path/route choice literature, using both SP-and RP-based studies Broach, Dill, and Gliebe (2012) and Sener, Eluru, and Bhat (2009) found that route utility was reduced by high-traffic crossings, stop signs, and traffic signals.…”
mentioning
confidence: 99%